Fuzzy logic control electromagnetic actuated CVT system - Rahman, Mohammed Ataur; Sazzad, Sharif; Sadakatul, SMS Bari (Taylor & Francis Ltd., 2011)
Fuzzy logic control electromagnetic actuator (EMA) is developed in this study to control the CVT of passenger car. The EMA development is conducted by two sets of electromagnetic actuators (solenoid) located on primary and secondary pulley. A set of solenoids are attached to the primary and secondary pulley to develop the attraction and repulsive forces. The relationships between the speed ratio and electromagnetic actuation and clamping force and output torque of the CVT are established based on the kinematics of the EMA-CVT system. A Fuzzy Logic Controller (FLC) is developed to control the EMA precisely based on the feedback of the RPM sensor and slope sensor. The EMA-CVT performance with controller has found 28% more than the performance of the EMA-CVT without controller. The solenoids of the EMA were activated by varying the current supply with the Fuzzy-Proportional-Derivative-Integrator (FPID) to maintain the non-linearity of the CVT in response of the vehicle traction torque demand. Result shows that the solenoid able to pull the plunger in the desired distance with supply current of 12.5 amp while push the plunger to the desired distance with 14.00 amp current supply to the windings when the vehicle is considered in 10% grad. The acceleration time of the ¼ scale car has been recorded as 5.5 s with the response of the traction of the car.